Dejavniki poklicnih sprememb in deprofesionalizacija poklicev v družbi znanja - Pavlin, Samo (Teorija in praksa, 2006)
The main purpose of the paper is to identify the occupational changes and explain how vulnerable is the structure of occupational assignments and competencies in the knowledge society. The paper is a case study of a middle manager in the hotel industry of the tourist centre Krakow in Poland. The article begins with the presentation of classical theory of professions and continues with a discussion of de-professionalisation. It continues with a description of sectoral trends and on the basis of the case study it attempts to identify the key factors that affect changes of the occupational roles. We conclude with an assessment on how these factors are related to different dimensions of occupational professionalisation: working assignments that are relatively continuous and sustainable, and how they are connected to the occupational identity, occupational ethic and occupational organisation.
Keywords: Occupations; Poklici; Profesionalizacija; Professionalization; Managerji; Managers; Tourism; Turizem; Poland; Poljska; družba znanja; deprofesionalizacija; poklicne spremembe